The Seagrass Leaf Waste Flour Addition To Feed For Color Pigment Enhance-ment Of Koi Fish (Cyprinus rubrofuscus): English - Fahruddin, Muh; Aldi, Davit; Ilyas, Anita Prihatini (Journal of Aquaculture and Fish Health, 2025)
The price of ornamental fish is determined by the quality of the color of ornamental fish, but in general, the color of ornamental fish will fade when maintained in an aquarium container. The purpose of this study was to determine the color pigment content of koi fish (Cyprinus rubrofuscus) after being given additional feed in the form of seagrass leaf waste flour Thalassia hemprichii.  This research was conducted for 28 days. This study used a completely randomized design (RAL) with 5 treatments and 3 replicates so that in this study there were 15 experimental units. The treatment in this study was the addition of seagrass leaf waste flour to fish feed. P1 (control), P2 (addition of 3% seagrass leaf waste flour), P3 (addition of 6% seagrass leaf waste flour), P4 (addition of 9% seagrass leaf waste flour), and P5 (addition of 12% seagrass leaf waste flour). The results showed that the value of color pigment content in all treatments were P1 21.56 µmol/g, P2 22.75 µmol/g, P3 23.49 µmol/g, P4 22.08 µmol/g and P5 25.76 µmol/g. For absolute growth in all treatments, P1 was 1.37 g, P2 1.53 g, P3 1.80 g, P4 2.73 and P5 3.70 g. For absolute growth in all treatments, P1 was 53%, P2 67%, P3 67%, P4 80% and P5 87%. The survival rate of ornamental Koi (C. rubrofuscus) in all treatments was P1 53%, P2 67%, P3 67%, P4 80%, and P5 87%. This research concludes that the color pigment content of ornamental Koi (C. rubrofuscus) increases after feeding additional doses of T. hemprichii and the best color pigment increase is shown by treatment P5 with the addition of a 12% dose of T. hemprichii, namely 25.76 µmol/g.